THE QUALITY OF CONTENT, PROCESS AND OUTCOMS OF HIGHER EDUCATION FROM THE STUDENTS' VIEWPOINT - D. A. Kalugina (Russian State Vocational Pedagogical University, 2015)
The paper reveals the survey findings investigating the students' attitude to the higher education quality. The education quality concepts are considered in pedagogical, economic and sociological context; the main aspects of education quality involve: the compliance with the existing norms and standards, and correspondence with students' personal requirements for professional training.The comparative analysis of the above survey findings demonstrates that the students' idea of education quality is based on the teaching staff professionalism, implementation of new educational technologies and individual approach. Students at a technical state university emphasized the high level of professional training, adaptive abilities development and career prospects; while students at private classical universities valued personal and cultural qualities, and fundamental knowledge. Few of the surveyed students mentioned the normative content aspect of education quality - compliance with the state educational standards. Therefore, the author proves the need for acquainting students with the above standards in their respective profiles.The research findings can be applied for optimizing the training process in the higher educational establishments.